Design and Performance Analysis of Multirate-NOMA - Hamad Yahya; Emad Alsusa; Arafat Al-Dweik (IEEE Open Journal of the Communications Society)
non-orthogonal multiple access (NOMA) is a promising candidate to improve the spectral efficiency by multiplexing users in the power-domain. Most of the work in the literature considers the analysis of the single-rate (SR)-NOMA, which can only vary the power per user, limiting its flexibility and bit error rate (BER) performance. Therefore, this work considers the design and performance analysis of multirate (MR)-NOMA, which controls the symbol energy per user by varying the symbol rate and power simultaneously. Both joint-multiuser maximum likelihood sequence detector (JMLSD) based on the maximum liklihood criterion and a novel low-complexity optimal successive interference cancellation (SIC) receiver are designed. Furthermore, closed-form BER expressions are derived considering arbitrary symbol rates and modulation orders. The derived expressions are then used to optimize the power allocation at the base station (BS) to minimize the BER while strictly satisfying certain BER requirements. The presented results show that MR-NOMA offers more trade-off freedom between spectral efficiency and robustness to errors. As such, MR-NOMA can have up to two orders of magnitude improvement in BER performance in some scenarios. The derived expressions are validated via simulations.